Analysis of Microorganism Diversity in Haemaphysalis longicornis From Shaanxi, China, Based on Metagenomic Sequencing - Cao, Runlai; Ren, Qiaoyun; Luo, Jin; Tian, Zhancheng; Liu, Wenge; Zhao, Bo; Li, Jing; Diao, Peiwen; Tan, Yangchun; Qiu, Xiaofei; Zhang, Gaofeng; Wang, Qilin; et al. (Frontiers in Genetics, 2021)
Ticks are dangerous ectoparasites of humans and animals, as they are important disease vectors and serve as hosts for various microorganisms (including a variety of pathogenic microorganisms). Diverse microbial populations coexist within the tick body. Metagenomic next-generation sequencing (mNGS) has been suggested to be useful for rapidly and accurately obtaining microorganism abundance and diversity data. In this study, we performed mNGS to analyze the microbial diversity of Haemaphysalis longicornis from Baoji, Shaanxi, China, with the Illumina HiSeq platform. We identified 189 microbial genera (and 284 species) from ticks in the region; the identified taxa included Anaplasma spp., Rickettsia spp., Ehrlichia spp., and other important tick-borne pathogens at the genus level as well as symbiotic microorganisms such as Wolbachia spp., and Candidatus Entotheonella. The results of this study provide insights into possible tick-borne diseases and reveal new tick-borne pathogens in this region. Additionally, valuable information for the biological control of ticks is provided. In conclusion, this study provides reference data for guiding the development of prevention and control strategies targeting ticks and tick-borne diseases in the region, which can improve the effectiveness of tick and tick-borne disease control.